The physics aspect of price index changes: Superdiffusive approach - Kantawong Vuttivorakulchai (2018)
Attempts were made to quantify the buying and selling interaction of worldwide financial markets into quantitative findings. We introduce a probability density derived from non-extensive Tsallis statistical mechanics that can be applied to the interpretation of percent price index changes for important indices such as NYSE Composite, DJIA, S & P 500, NASDAQ Composite, FTSE 100, NIKKEI 225, Hang Seng, Straits Times and SET index. Results of applying Tsallis' probability density through markets' observation illustrated the behavior of all indices indicating super diffusive dynamics. Furthermore, an Ito-Langevin equation with a time-dependent diffusion coefficient and the nonlinear Fokker-Planck equation can exhibit investment risk of each price index. Finally, we not only explained the complex behavior of financial indices in Physics aspect, but simplified it into quantitative meanings able to be virtually used further as well. © 2011 Academic Journals.